Transformasi Digital Sistem Pembayaran di Indonesia: Studi atas Peran QRIS - Dedi Harianto Dedi; Ahmad (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
One of the most important aspects of Indonesia's economic modernization is the payment system's digital transformation. The purpose of this study is to investigate how the Quick Response Code Indonesian Standard (QRIS) contributes to the rapid digitization of the country's financial system. This study examines the advantages, difficulties, and effects of QRIS deployment on financial inclusion and transaction efficiency using a descriptive-qualitative methodology. The results show that, especially during the pandemic, QRIS speeds up the transition to cashless transactions, promotes adoption among MSMEs, and streamlines digital payment systems. To overcome implementation issues, however, digital infrastructure and literacy must be strengthened.